Anti-fungal hevein-like peptides biosynthesized from quinoa cleavable hololectins - Loo, Shining (2022)
Chitin-binding hevein-like peptides (CB-HLPs) belong to a family of cysteine-rich peptides that play important roles in plant stress and defense mechanisms. CB-HLPs are ribosomally synthesized peptides that are known to be bioprocessed from the following two types of three-domain CB-HLP precursor architectures: cargo-carrying and non-cargo-carrying. Here, we report the identification and characterization of chenotides biosynthesized from the third type of precursors, which are cleavable hololectins of the quinoa (Chenopodium quinoa) family. Chenotides are 6-Cys-CB-HLPs of 29-31 amino acids, which have a third type of precursor architecture that encompasses a canonical chitin-binding domain that is involved in chitin binding and anti-fungal activities. Microbroth dilution assays and microscopic analyses showed that chenotides are effective against phyto-pathogenic fungi in the micromolar range. Structure determination revealed that chenotides are cystine knotted and highly compact, which could confer resistance against heat and proteolytic degradation. Importantly, chenotides are connected by a novel 18-residue Gly/Ala-rich linker that is a target for bioprocessing by cathepsin-like endopeptidases. Taken together, our findings reveal that chenotides are a new family of CB-HLPs from quinoa that are synthesized as a single multi-modular unit and bioprocessed to yield individual mature CB-HLPs. Importantly, such precursors constitute a new family of cleavable hololectins. This unusual feature could increase the biosynthetic efficiency of anti-fungal CB-HLPs, to provide an evolutionary advantage for plant survival and reproduction.